2020
DOI: 10.1097/ncc.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Experiences of Parenting Young Children While Battling Breast Cancer in Taiwan

Abstract: Background Western mothers with breast cancer find themselves struggling with parenting responsibilities. Because parenting is culturally shaped, literature on ill mothers' experiences of parenting young children from a collectivist culture is limited. Objective The aim of this study was to examine Taiwanese mothers' experiences of and cultural practices embedded in parenting young children while in treatment for breast cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Some preadolescent children were conscious of changes in maternal discipline and felt obligated to live up to their ill mothers' expectations, including high self-reliance, well-mannered behaviour, and good school performance. This loosening of disciplinary practices fits with Asian mothers' self-reporting of a letting-go mindset after a breast cancer diagnosis (Chin et al, 2020;Kim et al, 2012). Interestingly, Taiwanese children view studying hard as their major duty and the best they can do during their mothers' illness, reflecting the emphasis of academic success in Asian cultures (Shek, 2007;Xia et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…Some preadolescent children were conscious of changes in maternal discipline and felt obligated to live up to their ill mothers' expectations, including high self-reliance, well-mannered behaviour, and good school performance. This loosening of disciplinary practices fits with Asian mothers' self-reporting of a letting-go mindset after a breast cancer diagnosis (Chin et al, 2020;Kim et al, 2012). Interestingly, Taiwanese children view studying hard as their major duty and the best they can do during their mothers' illness, reflecting the emphasis of academic success in Asian cultures (Shek, 2007;Xia et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…Spiritual support care needs were reported in 6 (13%) articles and included needs surrounding search for meaning and existential needs and struggles. Chin et al (2021) found that there is a need in Chinese parent’s to maintain one’s health and strong will for survival which is fundamental in maintaining “familial piety” (p. E198).…”
Section: Resultsmentioning
confidence: 99%
“…care needs were reported in 6 (13%) articles and included needs surrounding search for meaning and existential needs and struggles. Chin et al (2021) found that there is a need in Chinese parent's to maintain one's health and strong will for survival which is fundamental in maintaining "familial piety" (p. E198). Practical: Practical supportive care needs are defined as "needs for direct assistance in order to accomplish a task or activity and thereby reduce the demands on the person" (Fitch, 2008: 9).…”
Section: Table 2 (Continued)mentioning
confidence: 99%
“…Taiwanese BCD mothers described suffering from a newly distant relationship with their children, including loss of physical contact and intimate interactions. The attachment has been described as a major issue in young children with ill mothers in that they have difficulty separating from their mothers (Hauken et al, 2018); in response to maternal separation, they tend to transfer their proximity‐seeking behaviours to other family members (Chin et al, 2021). Our finding showed that, while children endure stressful separations, mothers also suffered from a feeling of loss from their children not being as attached to them.…”
Section: Discussionmentioning
confidence: 99%